2003
DOI: 10.1017/s0022029903006435
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Fourier transform infrared spectrometry in determination of casein in dairy cows' milk

Abstract: For practical purposes the casein content of milk is often estimated from the crude protein content using a general conversion factor. This is done even though it is known that several factors can influence the percentage of casein nitrogen in the total nitrogen (casein number). The uncontrolled variation in casein number affects optimization of cheese production because casein is a limiting factor for cheese yield. Fourier transform infrared spectrometry has recently been introduced for casein determination. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
1
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 0 publications
2
11
1
3
Order By: Relevance
“…This result is in contrast with other reports that indicate a generally higher casein number for Jersey milk (Ng-Kwai-Hang et al 1986;NgKwaiHang and Kim 1996;Sorensen et al 2003). Even though the lactation stage is known to affect the casein number of cow's milk (Barbano et al 1991;Blake et al 1980), this was in the present analysis not found to be significant, perhaps because the relationship between casein number and lactation stage is complex and cannot be assumed to be the same for all breeds.…”
Section: Discussioncontrasting
confidence: 85%
“…This result is in contrast with other reports that indicate a generally higher casein number for Jersey milk (Ng-Kwai-Hang et al 1986;NgKwaiHang and Kim 1996;Sorensen et al 2003). Even though the lactation stage is known to affect the casein number of cow's milk (Barbano et al 1991;Blake et al 1980), this was in the present analysis not found to be significant, perhaps because the relationship between casein number and lactation stage is complex and cannot be assumed to be the same for all breeds.…”
Section: Discussioncontrasting
confidence: 85%
“…Similarly, MIR indicators of protein fractions such as casein and lactoglobulin (Barbano and Dellavalle, 1987;Sorensen et al, 2003) have been obtained. As it is possible to determine the total content of protein and some specific milk proteins, it could be possible to predict the LTF content of milk using MIR as LTF is a natural milk glycoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…A espectroscopia no infravermelho já foi aplicada em leite para determinação de caseína 44 , proteína e lactose 45 , bem como para classificação 46 de leite e em casos de adulteração com gordura 47 , e com soro em leite em pó desnatado.…”
Section: A Espectroscopia Por Reflectância Difusa No Infravermelho Prunclassified